Takhrij and Syarah Hadith of Chemistry: Prohibition of Blowing Food and Drink - Hani Alvianingsih; M. Solahudin (International Journal on Orange Technologies, 2021)
This study aims to discuss the hadith of the Prophet Muhammad SAW. namely about the prohibition of blowing food and drink. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research are the dangers of blowing food and drinks from a chemical perspective. The conclusion of this research is takhrij and syarah hadith of the Prophet about the prohibition of blowing food and drink that can cause disease.